Anakinra in hospitalized patients with severe COVID-19 pneumonia requiring oxygen therapy: Results of a prospective, open-label, interventional study. (February 2021) - Balkhair, A.; Al-Zakwani, I.; Al Busaidi, M.; Al-Khirbash, A.; Al Mubaihsi, S.; BaTaher, H.; Al Aghbari, J.; Al Busaidi, I.; Al Kindi, M.; Baawain, S.; Al Alawi, A.; Al Lawati, A.; et al.
Highlights: Anakinra averted the need for mechanical ventilation in patients with severe COVID-19 pneumonia. Anakinra accelerated weaning off oxygen therapy and hastened transition to ambient air. Patients treated with anakinra showed significant reduction in biomarkers of inflammation. The study results did not demonstrate a significant difference in in-hospital mortality. This study provided further evidence for the utility of anakinra in severe COVID-19 pneumonia. Abstract: Objective: The aim of this study was to evaluate the efficacy of anakinra in patients who were admitted to hospital for severe COVID-19 pneumonia requiring oxygen therapy. Methods: A prospective, open-label, interventional study in adults hospitalized with severe COVID-19 pneumonia was conducted. Patients in the interventional arm received subcutaneous anakinra (100 mg twice daily for 3 days, followed by 100 mg daily for 7 days) in addition to standard treatment. Main outcomes were the need for mechanical ventilation and in-hospital death. Secondary outcomes included successful weaning from supplemental oxygen and change in inflammatory biomarkers. Outcomes were compared with those of historical controls who had received standard treatment and supportive care. Results: A total of 69 patients were included: 45 treated with anakinra and 24 historical controls. A need for mechanical ventilation occurred in 14 (31%) of the anakinra-treated group and 18 (75%) of the historical cohort ( p < 0.001). In-hospital death occurred in 13 (29%) of the anakinra-treated group and 11 (46%) of the historical cohort ( p = 0.082). Successful weaning from supplemental oxygen to ambient air was attained in 25 (63%) of the anakinra-treated group compared with 6 (27%) of the historical cohort ( p = 0.008). Patients who received anakinra showed a significant reduction in inflammatory biomarkers. Conclusion: In patients with severe COVID-19 pneumonia and high oxygen requirement, anakinra could represent an effective treatment option and may confer clinical benefit. Trial registration number: ISRCTN74727214.